INDICATORS AND CRITERIA FOR EVALUATION OF THE EFFECTIVENESS OF BORDER SUBDIVISION DURING THE SPECIAL PERIOD - Anatoly Fedorchuk; Andrii Dobrovolskyi; Dmitry Kovalyov (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
This report proposes a system of indicators and criteria for assessing the effectiveness of border subdivision during the special period. For the formation of indicators and criteria in the first priority was the selection of tasks that are based on the border subdivisions during the Joint Forces Operation. The selection of indicators and criteria was made for a specific case, based on the tasks that were set before the subdivision. In the future, with the help of indicators and criteria, we will be able to construct complex models to assess the effectiveness of border subdivision for a specific task. This report will develop the existing approach to the formation of indicators and criteria for assessing the effectiveness of special forces and other facilities. The proposed set of indicators and criteria may vary. It depends on the specificity of the task conditions.